2018
DOI: 10.1097/tp.0000000000002105
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients Supported With Continuous-flow Left Ventricular Assist Device Have a Sufficient Risk of Death to Justify a Priority Allocation? A Propensity Score Matched Analysis of Patients Listed in UNOS Status 2

Abstract: Survival of patients listed in UNOS status 2 who receive a CF-LVAD while listed is significantly lower compared to patients who do not receive mechanical support on the waiting list. The current priority in the allocation system given to patients on CF-LVAD seems justified. Further posttransplant survival is not negatively influenced by previous CF-LVAD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…13 In some selected studies, durable VAD also demonstrated a non-inferior effectiveness in long-term survival efficiency compared with those without MCS. 14,15 Few studies have been designed to investigate the impact of timing issue in relation to the post-transplant result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In some selected studies, durable VAD also demonstrated a non-inferior effectiveness in long-term survival efficiency compared with those without MCS. 14,15 Few studies have been designed to investigate the impact of timing issue in relation to the post-transplant result.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of MCS on the post‐transplant outcome, most studies focus on the different types of MCS association with the posttransplant outcome, and ECMO had an inferior outcome compared with those supported by VAD 13 . In some selected studies, durable VAD also demonstrated a non‐inferior effectiveness in long‐term survival efficiency compared with those without MCS 14,15 . Few studies have been designed to investigate the impact of timing issue in relation to the post‐transplant result.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] In the past decade, approximately 40% of the patients listed for HT were bridged with an LVAD. 2,[7][8][9] In October 2018, the HT allocation system in the United States changed from a 3-tier system to a 6-tier system with a focus to differentiate priority amongst the sickest even further. The newer allocation system prioritizes patients with cardiogenic shock with temporary mechanical circulatory support (MCS) devices and assigns a low priority to stable LVAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous flow LVADs have been approved for use as bridge to transplant since 2007 and over time have been improved to reduce complications 3–6 . In the past decade, approximately 40% of the patients listed for HT were bridged with an LVAD 2,7–9 …”
Section: Introductionmentioning
confidence: 99%